Evaluation of the effectiveness of an organic fertilizer in the cultivation of paprika (Capsicum annuum L.) on the farm of the Carare Integrated School (CICA) located in the municipality of Cimitarra - Santander-Colombia. - Ochoa Fandiño, Adriana
Poultry manure is a widely used organic fertilizer due to its high content of nutrients such as nitrogen, phosphorus and potassium. It is produced from the decomposition and accumulation of poultry droppings, mainly hens, in combination with the material used to absorb moisture. Poultry manure is used to improve soil quality and structure, as well as to increase crop production. In the present work, the effect of poultry manure in combination with efficient microorganisms (EM) on the cultivation of paprika (Capsicum annuum L.) is evaluated. The farm of the Colegio Integrado del Carare has a problem of solid waste production from the feces of 600 laying hens, generating approximately 2 tons of solid waste per year. On the other hand, there are problems in the production of chicken manure because its preparation is not adequate and causes environmental problems. Therefore, the aim is to develop a biotechnological strategy to improve the production of poultry manure with the addition of efficient microorganisms (EM) and to use poultry manure as agricultural fertilizer to improve paprika production. The hypothesis is that the application of poultry manure with and without microorganisms will improve paprika crop growth, quality and production. The methodology used is the preparation of the poultry manure with EM, the establishment of the crop and the application of treatments. Treatments consist of grams of poultry manure/plant: absolute control (0 gr), treatment 1 (80 gr), treatment 2 (40 gr), treatment 3 (6 gr), and grams of poultry manure/plant + ME - absolute control 0 gr - treatment 1 (80 gr) - treatment 2 (80 gr + 10% ME) - treatment 3 (80 gr + 25% ME) - treatment 3 (80 gr + 50% ME). The statistical design is a completely randomized design with 6 replicates per treatment, and significant differences between treatments are evaluated by ANOVA and t-test. The impact we want to generate is to contribute to sustainable agricultural practices in the cultivation of paprika and the preservation of the environment through the proper preparation of poultry manure.